PENGARUH ETIKA PROFESI, EFIKASI DIRI, KECERDASAN SPIRITUAL, KECERDASAN INTELEKTUAL, DAN KECERDASAN EMOSIONAL TERHADAP KINERJA AUDITOR - Puspita Dewi, I Gusti Ayu; Tenaya, Agus Indra (E-Jurnal Akuntansi; Vol 19 No 1 (2017), 2017)
This study aimed to determine the effect of professional ethics, self-efficacy, spiritual intelligence, intellectual intelligence, and emotional intelligence on auditor performance. This study was conducted in the Bali provincial Public Accounting Firm registered in the Directory of Certified in 2016 with the total of a population was 50 auditors. The sampling method used in this study is the technique of saturated samples and the total samples that used were 42 auditors from 6 Public Accounting Firm. The data collection is done by distributing questionnaires using 4 points Likert scale to measure 29 indicators. The analysis technique used Partial Least Square. The results showed that professional ethics, self-efficacy, spiritual intelligence, intellectual intelligence, and emotional intelligence had the positive effect on auditor performance.
Keywords: professional ethics, self-efficacy, spiritual intelligence, intellectual intelligence, emotional intelligence